Gaucher disease: Enfermedad de gaucher - Mendoza-Quispe, Magaly (2018)
Gaucher's disease (GD), an autosomal recessive disease, is the most frequent of the group of lysosomal storage diseases. The symptoms and signs are multisystemic, are established chronically and progressively and are due to the accumulation of glucocerebrosides in the bone marrow, spleen, liver, lungs, skeletal tissue and in the brain. There are three types of disease presentation: Type I (the most common), Type II and Type III. It is important to make an early diagnosis because patients can benefit from enzyme replacement therapy (ERT). Key words: Gaucher disease; Diagnosis; Treatment. (source: MeSH NLM)   DOI: 10.25176/RFMH.v18.n2.1288